Maintenance Management of Indoor Facilities at Kindergarten of Pertiwi 1 Kantor Gubernur Padang - trisna, tetin eka (Jurnal Ilmiah Pesona PAUD, 2018)
This study aims to describe the maintenance management of indoor facilities in TK Pertiwi 1 Kantor Gubernur Padang. The research method used is descriptive method with qualitative approach. The results showed that the maintenance management of indoor facilities in Kindergarten of Pertiwi 1 Kantor Gubernur Padang was not implemented properly because it did not have a written SOP about the use and maintenance of facilities, unscheduled supervision and no special record of maintenance that has been done. However, in activity of maintenance, it has been done quite well. Activity forms of maintenance which is conducted in Kindergarten of Pertiwi 1 Kantor Gubernur Padang, namely: 1) Activity of maintenance implemented continuously; 2) Periodically maintenance; 3) Emergency maintenance; and 4) preventive maintenance.